CEO Demographical characteristics and financial reporting timeliness in Nigeria: Moderated by research and development investment - Ahmad Muhammed Lawal; Noor Afza Amran; Nor Atikah Shafai (Cogent Business & Management, 2024)
The International Accounting Standard Boards highlighted financial reporting timeliness (FRT), as one of the qualitative attributes taken into consideration when measuring financial reporting quality (FRQ). Considering that the board is the main internal corporate governance (CG) mechanism, the attributes of Chief Executive Officers (CEOs) are predicted to be associated with the FRT. The study aims to analyse the impact of CEO demographic characteristics on the FRT of non-financial listed companies in Nigeria. The sample consisted of 86 listed non-financial companies' annual reports on the Nigeria Stock Exchange (NSE) for 2015–2021. Multiple linear regressions were used in analysing the collected data via STATA software. Results revealed that 6 out of 10 hypotheses were significantly related to FRT. Findings indicated that CEO characteristics may encourage managers to reduce reporting lag, increase the quality of financial reports, and signal good news to shareholders, which may significantly affect the company's performance. It is recommended that stakeholders review CG and accounting standards reform to improve FRT and deter managers from late submission of financial statements to the NSE. The study contributes to stakeholders like managers, regulatory bodies, policymakers, and professional bodies to enhance current standards, and regulations in Nigeria. Finally, agency theory and upper echelons theory were used to delve into new findings based on the Nigerian setting and enhance the rigour, coherence, and impact of this study within its academic or practical domain.
Keywords: 650; CEO demographics; Financial reporting; nigeria; non-financial sectors; timeliness